PILARISASI BENTONIT DENGAN MODIFIKASI PENAMBAHAN ASAM SULFAT SEBAGAI KATALIS ASAM PADAT DALAM ESTERIFIKASI - Hery Haerudin; Dona Sulistia Kusuma; Ermawan Ermawan; Isna Komalasari (Jurnal Teknik Kimia Indonesia, 2005)
Preparations of pillared bentonites have been carried out using refined bentonite from Trenggalek, East Java, Indonesia as raw materials. Modification cations of pillarization method has been accomplished by the introduction of treatment in acid solution at various stages of pillarization procedure, specifically (i) prior to ion-exchange, (ii) subsequent to ion-exchange, (iii) subsequent to drying of ion-exchanged bentonite and (iv) subsequent to calcination of ion-exchanged bentonite. The resulted modified clays were characterized by X-ray diffraction spectrometry, N2-adsorption, TG/DT Analysis and SEM. Shifts of pore distributions to the Larger pore size by the introduction of acid treatment on the pillarization procedure were observed, which are also accompanied by appropriate increase in specific surface area. Treatment in acidic solution may have resulted in removal of exchangeable cations, which lightened AL-polycation intercalation during the pillarization. The modified clays were tested in an esterification reaction model using stearic acid and ethanol as reaction partners. Activity tests showed that enhancement in physco-chemical characteristics such as specific surface area, pore size and pore distribution, was not generally followed by the increase of the activity. Key Words: Bentonite, Pillarization, Acid Treatment, Solid Acid, Esterification, Activity.